Investigation of the Lipid-Lowering Mechanisms and Active Ingredients of Danhe Granule on Hyperlipidemia Based on Systems Pharmacology - Chen, Kuikui; Ma, Zhaochen; Yan, Xiaoning; Liu, Jie; Xu, Wenjuan; Li, Yueting; Dai, Yihang; Zhang, Yinhuan; Xiao, Hongbin (Frontiers in Pharmacology, 2020)
Objective Investigate the active ingredients and underlying hypolipidemic mechanisms of Danhe granule (DHG). Methods The lipid-lowering effect of DHG was evaluated in hyperlipidemic hamsters induced by a high-fat diet. The ingredients absorbed into the blood after oral administration of DHG in hamsters were identified by ultra-high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF/MS). A systems pharmacology approach incorporating target prediction and network construction, gene ontology (GO) enrichment and pathway analysis was performed to predict the active compounds and map the compounds-targets-disease network. Real-time polymerase chain reaction (RT-PCR) and Western blot were utilized to analyze the mRNA and protein expression levels of predicted targets. Results DHG remarkably lowered the levels of serum total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-c), and arteriosclerosis index (AI), at the same time, elevated the levels of serum high-density lipoprotein cholesterol (HDL-c) and HDL-c/TC ratio in hyperlipidemic hamsters. Sixteen ingredients absorbed into blood after oral administration of DHG were identified as the possible components interacted with targets. Moreover, 65 potential targets were predicted after targets intersection and compounds–targets–disease network mapping. Then, compounds–targets–pathways network mapping revealed that six active compounds (emodin, naringenin, etc.) compounds could interact with 10 targets such as sterol regulatory element binding protein (SREBP) 1c, SREBP-2 and peroxisome proliferation-activated receptor (PPAR) α, regulate three lipid metabolism-related pathways including SREBP control of lipid synthesis pathway, PPAR signaling pathway and nuclear receptors in lipid metabolism and toxicity pathway, and further affect lipid metabolic processes including fatty acid biosynthesis, low-density lipoprotein receptor (LDLR)-mediated cholesterol uptake, bile acid biosynthesis, and cholesterol efflux. Experimental results indicated that DHG significantly increased SREBP-2, LDLR, PPARα, liver X receptor alpha (LXRα), cholesterol 7α-hydroxylase (CYP7A1), and ATP binding cassette subfamily A member 1 (ABCA1) mRNA and protein expressions while decreased SREBP-1c and fatty acid synthase (FAS) mRNA, and protein expressions. Conclusion DHG possessed a good hypolipidemic effect that may be through affecting the mRNA and protein expressions of SREBP-1c, FAS, SREBP-2, LDLR, PPARα, LXRα, CYP7A1, and ABCA1, involving in fatty acid synthesis, LDLR-mediated cholesterol uptake, bile acid biosynthesis, and cholesterol efflux. This study further provided experimental evidence about its practical application for treating hyperlipidemia and its complications.